A bit arbitration tree anti-collision protocol in radio frequency identification systems. (November 2017) - Fu, Yu; Wang, Xue; Wang, Enshu; Qian, Zhihong
Radio frequency identification technology has been extensively used in various practical applications, such as inventory management and logistics control. When numerous tags respond to reader simultaneously, tags-to-tag collision occurs and causes the reader to identify tags unsuccessfully. Therefore, how to reduce tag collisions has already emerged as an urgent and crucial problem to be solved for speeding up the identification operation. This article designs a characteristic-value-based grouping rule and a collision bits rule to determine transmitted bit string combinations accurately and proposes a bit arbitration tree anti-collision protocol based on these two rules to decrease the time for collecting all tag IDs. Furthermore, we consider the case that received bit string less than three bits, which occurs during the tag identification operation. Both theory and simulation analyses show that the proposed protocol can reduce the number of idle slots and total number of slots and thereby improve system efficiency.